Profile of Abnormal Cardiotocography and Perinatal Outcome at Term Pregnancy – A Descriptive Study in a Tertiary Centre of Nepal - Jigyasa Subedi; Deepanjali Sharma; Manoj Lamsal; Hasina Banu; Tara KC; Subash Chandra Sharma; Bekha Laxmi Manandhar (Journal of Universal College of Medical Sciences, 2025)
INTRODUCTION Identiﬁcation of fetal distress and intervention in time accordingly can have good perinatal health. Different modalities can be used for identifying fetal distress depending upon the resources and settings. This study aims to ﬁnd the abnormalities of cardiotocography (CTG) in identifying fetal distress and its utility in perinatal outcome. MATERIAL AND METHODS This was hospital based cross-sectional descriptive study for 6 months in patients with term pregnancy in cephalic presentation having abnormal CTG ﬁndings. RESULTS Out of 198 patients, 53% were multigravidae. Variable deceleration was seen in 74 (37.3%), late deceleration was notiﬁed in 30 (15.1%), and persistent tachycardia was seen in 22 (11.1%). Meconium stained liquor was observed in 114 (57.6%). Cord around neck was present in 40 (20.2%). APGAR score less than 7 at 5 minutes was notiﬁed in 120 (59.4%), reception of resuscitation was in 100 (50.5%), NICU admission was done in 50 (25.2%), neonatal deaths within 72 hours were 4 (2%) which were observed in CTG with variable and late deceleration, however no still birth was recorded. CONCLUSION Cardiotocography interpretations help in identifying fetal distress which in-turn determines the perinatal outcome.